2017
DOI: 10.3758/s13423-017-1286-8
|View full text |Cite
|
Sign up to set email alerts
|

The anchoring bias reflects rational use of cognitive resources

Abstract: Cognitive biases, such as the anchoring bias, pose a serious challenge to rational accounts of human cognition. We investigate whether rational theories can meet this challenge by taking into account the mind's bounded cognitive resources. We asked what reasoning under uncertainty would look like if people made rational use of their finite time and limited cognitive resources. To answer this question, we applied a mathematical theory of bounded rationality to the problem of numerical estimation.Our analysis le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
129
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(150 citation statements)
references
References 108 publications
(212 reference statements)
4
129
0
2
Order By: Relevance
“…Ethical considerations should never be overlooked when putting prediction models into practice. Previous studies on anchoring effects suggested that the process of human decision making is easily influenced by an initial piece of information (LACE index or HOSPITAL score in the current study), which is hard to avoid [43]. Moreover, a certain portion (10% to 20%) of patients with high risk for readmission would be falsely stratified as low risk using either the LACE index or HOSPITAL score model.…”
Section: Discussionmentioning
confidence: 73%
“…Ethical considerations should never be overlooked when putting prediction models into practice. Previous studies on anchoring effects suggested that the process of human decision making is easily influenced by an initial piece of information (LACE index or HOSPITAL score in the current study), which is hard to avoid [43]. Moreover, a certain portion (10% to 20%) of patients with high risk for readmission would be falsely stratified as low risk using either the LACE index or HOSPITAL score model.…”
Section: Discussionmentioning
confidence: 73%
“…Over the years this idea has been rejected by many investigators (e.g., Epley & Gilovich, 2005;Kahneman, 2011, ch. 11) but we argue that this rejection is premature (see Lieder, Griffiths, Huys, & Goodman, 2018;Newell & Shanks, 2014, for fuller discussion). Evidence that anchoring is an automatic (or System 1; Kahneman, 2011) process has come, for instance, from demonstrations that it is largely immune to increased motivation to be accurate, induced by financial incentives (Chapman & Johnson, 2002), but more recent work has led to revision of this conclusion (Simmons, LeBoeuf, & Nelson, 2010).…”
Section: Discussionmentioning
confidence: 93%
“…Just as with studies on incentives, several early reports suggested no effect of expertise (e.g., Northcraft & Neale, 1987), but more recent research challenges this conclusion (Smith, Windschitl, & Bruchmann, 2013). Lieder et al (2018) showed that many of the benchmark properties of anchoring can be explained by a deliberative, rational resource model.…”
Section: Discussionmentioning
confidence: 98%
“…The limited resources lead to the metareasoning problem, which concerns the optimal deployment of the available computational power (7,8,74,75). It is a decision problem about which of the various options to evaluate internally ( Figure 2).…”
Section: Metareasoningmentioning
confidence: 99%